A comparison on untreated and alkaline treated rubberwood flour on physical and mechanical properties of wood plastic composites. (2018) - Khamtree, Sriwan; Ratanawilai, Thanate; Ratanawilai, Sukritthira
The effect of the untreated and alkaline treated rubberwood flour (RWF) on water absorption, tensile and flexural properties of the wood plastic composites (WPCs) was investigated. The surface of RWF was treated by an alkaline treatment with NaOH solution of 2% w/v concentration for 24 h. The results showed that the RWF treated with alkaline could enhance the interfacial adhesion with rPP and also improve the water absorption and tensile and flexural properties of WPCs. In addition, the alkaline treatment and RWF content significantly affected the tensile and flexural strength. The alkaline treatment also increased water resistance of WPCs, which at 20% RWF content showed the lower water absorption (2.04%). The highest tensile strength (17.75 MPa) and flexural strength (35.73 MPa) of WPCs were achieved with an alkaline treatment at 30 wt% RWF. Moreover, the tensile and flexural modulus of WPCs increased with increasing RWF content (20% to 50%).